KING COCONUT - Nandanie D. Ediriweera, Ph.D. (International Coconut Community, 1996)
The king coconut (Thambili) which is characterized by its bright orange colour is said to have originated in Sri Lanka and is tertned cocos nucifera var. Aurantiaca. The diagnostic characters of varieties are mostly nut size, colour of epicarp, mesocarp and thickness of endosperm. Marco Polo, who passed through Sumatra more than seven hundred years ago described the coconut as containing an edible substance that is sweet and pleasant to the taste. He said, ‘the cavity of pulp is filled with the liquid clear as water, cool and better flavoured and more delicious than wine or any other kind of drink whatever’.